THE INFLUENCE OF BANK PERFORMANCE AND BI RATE ON BANK LENDING (Case Study of Listed Commercial Banks in Indonesia in the Period of January 2008 â€“ December 2012) - Pratiwi, Manda Rizka (Jurnal Ilmiah Mahasiswa FEB, 2014)
Using time series data from January 2008 to December 2012, this research aims at finding the dimensional influence of bank performance which consists of (1) Third Party Funds (DPK) (2) Capital Adequacy Ratio (CAR) and BI Rate on bank lending. After reviewing the current literature and testing the properties of individual time series data, Error Correction Model (ECM) is used along with t-test and F-test to reveal the relation and the influence of the pre-determined variables. The finding shows that Third Party Funds (DPK), CAR, and BI Rate have a significant influence on bank lending. In short-run, Third Party Funds and BI Rate have a positive and significant influence on bank lending and CAR has a negative and significant influence on bank lending. Meanwhile, in long-run CARt-1, BI Ratet-1, and ECTt-1 are not significant and thus do not affect bank lending. The most influential variable to the bank lending is Third Party Funds (DPK) which strongly affect bank lending in short-run and DPKt-1 that is likely to affect bank lending in long-run. Â  Keywords: Bank Lending, Third Party Funds, CAR, BI Rate